Large spin Hall effect of perpendicularly magnetized β-W/CoFeB/MgO layers with high thermal stability. (8th April 2019) - Wang, Lezhi; Shi, Kewen; Peng, Shouzhong; Cao, Kaihua; Yang, Huaiwen; Gao, Jianfeng; Zhao, Weisheng; Zhao, Chao
Abstract: We report a robust perpendicularly magnetized β -W/CoFeB/MgO multilayer structure. For the first time, we demonstrate efficient spin–orbit torque (SOT) switching and a highly thermally stable annealing process with this structure using X-ray diffraction tests, the harmonic technique, and SOT-driven magnetization switching measurements. These results may enable applications of SOT-based magnetic random access memory, which is required for integration in the CMOS back-end-of-line process.